2011
DOI: 10.1002/ejlt.201100103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of frying on the trans‐fatty acid formation in soybean oils

Abstract: To evaluate the effects of repeated deep-frying on the trans-fatty acid (TFA) formation in soybean oils, simultaneous frying experiments were carried out. French fries were prepared using three different types of soybean oil (pressed soybean oil, PSBO; first-grade solvent extracted soybean oil, FG-SESBO; and thirdgrade solvent extracted soybean oil, TG-SESBO). French fries were fried intermittently at 180-1858C for a total frying time of 32 h and at an interval time of 30 min. It was found that the initial amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The results showed that the linolenic acid was found absent in RBO + SOO (both ratios) after deep as well as shallow frying. Similarly, a recent study reported that linolenic acid present in soybean oil was less stable at high temperature (Hou, Jiang, & Zhang, 2012). The reduction in the USFA content during deep fat frying had also been reported in the previous studies (Che Man, Liu, Jamillah, & Rahman, 1999;Khatoon & Gopalakrishna, 2005).…”
Section: Fatty Acid (%)supporting
confidence: 75%
“…The results showed that the linolenic acid was found absent in RBO + SOO (both ratios) after deep as well as shallow frying. Similarly, a recent study reported that linolenic acid present in soybean oil was less stable at high temperature (Hou, Jiang, & Zhang, 2012). The reduction in the USFA content during deep fat frying had also been reported in the previous studies (Che Man, Liu, Jamillah, & Rahman, 1999;Khatoon & Gopalakrishna, 2005).…”
Section: Fatty Acid (%)supporting
confidence: 75%
“…Approximately 0.5 g frying oil was analysed in triplicates. The fatty acid composition was determined using GC as demonstrated by Hou et al (2012). Light petroleum/ diethyl ether mixture (90:10) was used to elute the nonpolar fraction.…”
Section: Oil Analysismentioning
confidence: 99%
“…AV was calculated as X = V 9 c 9 56.11/ m (V = volume in millilitres of standard volumetric potassium hydroxide solution; c = concentration of the standard volumetric potassium hydroxide solution; m = the mass in grams of the test sample). The fatty acid composition was determined using GC as demonstrated by Hou et al (2012).…”
Section: Oil Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…decades have witnessed numerous attempts to improve its oxidative stability, including partial hydrogenation, the addition of antioxidants, modification of fatty acids, and blending with more saturated or monosaturated oils to reduce the amount of polyunsaturated fatty acids [11][12][13][14]. In these methods, partially hydrogenated oils offer better resistance to thermo-oxidative degradation, but increases saturated fatty acid and trans-fatty acid which already have been reported to increase the ratio of low-density-lipoprotein (LDL) to high-density-lipoprotein cholesterol (HDL) in the plasma and increase the risk of coronary heart disease (CHD), and play a part in atherosclerosis development [15,16].…”
mentioning
confidence: 99%